The effect of hysterectomy and bilaterally salpingo-oophorectomy on sexual function in post-menopausal women - Celik, Husnu; Gurates, Bilgin; Yavuz, Adem; Nurkalem, Cemile; Hanay, Fethi; Kavak, Burcin (Elsevier Ireland Ltd, 2008)
Objective: To examine the effects of hysterectomy and bilaterally salpingo-oophorectomy (BSO) on Female Sexual Function Index (FSFI) in the post-menopausal women. Method: This study included 92 women who underwent vaginal hysterectomy (VH) and BSO (n:37) and who underwent abdominal hysterectomy (AN) and BSO (n:55). Estrogen replacement therapy (ERT) was given 21 women who underwent VH and BSO and 28 women who underwent AH and BSO in pre- and postoperative periods. All patients were evaluated preoperatively and postoperative 6th month in terms of FSFI Scores. Results: It was found that hysterectomies by abdominal or vaginal routes reduced FSFI scores significantly (P<0.05). The use of ERT were no effect on total score of FSFI in AH and BSO (P>0.05). ERT prevented deterioration of FSFI in women who underwent VH relative to preoperative values but AH. Conclusion: Hysterectomy causes unfavourable effects on sexual functions at least in the first 6 postoperative months and this negative effect can not be repaired by estrogen replacement therapy in AH and BSO. (C) 2008 Elsevier Ireland Ltd. All rights reserved.
Keywords: Female Sexual Function Index; Abdominal hysterectomy; Vaginal hysterectomy; Estrogen replacement therapy